2022
DOI: 10.29303/jppipa.v8i5.1534
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Attitudes towards the Environment in Students of Adiwiyata and Non-Adiwiyata Schools

Abstract: Environmental protection and preservation are in the hands of citizens and students are the future of the nation, so it is very important to assess or measure the attitude towards the environment owned by students. The aims of this research are to: (1) analyze the attitude towards the environment in students of Adiwiyata and Non-Adiwiyata schools on EBSS (Environmental Behavior Sub Scale), EOSS (Environmental Opinion Sub Scale), and EESS (Environmental Emotion Sub Scale); and (2) analyze the attitude towards t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…This means that as the quality of school life for adolescent students improves, it leads to a reduction in learned helplessness and vice versa. This finding is consistent with the results of previous studies (Button et al, 2013;Erlianti et al, 2023;Fais, 2017;Johnson et al, 2011;Kelly et al, 2016;Larashati et al, 2022;Lee et al, 2020;Li et al, 2011;Maba, 2022;Moreland et al, 2015;Oladele, 2014;Prihadi et al, 2018;Raufelder & Kulakow, 2021;Salminen et al, 2014;Wei & Chen, 2022;Wu & Tu, 2019;Yoong et al, 2015), suggesting that school life quality is an effective factor in reducing learned helplessness. These studies found that improving the quality of life for adolescent girls leads to better stress management and challenging situations, thereby reducing learned helplessness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This means that as the quality of school life for adolescent students improves, it leads to a reduction in learned helplessness and vice versa. This finding is consistent with the results of previous studies (Button et al, 2013;Erlianti et al, 2023;Fais, 2017;Johnson et al, 2011;Kelly et al, 2016;Larashati et al, 2022;Lee et al, 2020;Li et al, 2011;Maba, 2022;Moreland et al, 2015;Oladele, 2014;Prihadi et al, 2018;Raufelder & Kulakow, 2021;Salminen et al, 2014;Wei & Chen, 2022;Wu & Tu, 2019;Yoong et al, 2015), suggesting that school life quality is an effective factor in reducing learned helplessness. These studies found that improving the quality of life for adolescent girls leads to better stress management and challenging situations, thereby reducing learned helplessness.…”
Section: Discussionsupporting
confidence: 93%
“…It impacts both formal and informal aspects of school and is influenced by society, individual experiences, and peer relationships (Li et al, 2011). According to the findings of previous studies, school quality of life is positively related to better student learning, positive attitudes towards school, academic success, academic progress, acceptance of responsibility and commitment towards school tasks, a sense of belonging to school, academic self-concept, psychological well-being, academic enthusiasm, increased motivation for activity and achieving results, and happiness, and negatively related to the emergence of deviant behaviors and academic burnout (Button et al, 2013;Erlianti et al, 2023;Johnson et al, 2011;Kelly et al, 2016;Larashati et al, 2022;Lee et al, 2020;Li et al, 2011;Maba, 2022;Oladele, 2014;Raufelder & Kulakow, 2021;Salminen et al, 2014;Yoong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Health Promotion is related to new information that will be conveyed with the aim of introducing new information that will give rise to better changes. (Larashati et al, 2022;Pane & Patriana, 2016;Syah et al, 2021). The main characteristic of an innovation is the novelty factor.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Diffusion of innovation is a process where an innovation is communicated through certain communication channels over a certain period in a social system. Health Promotion is related to new information that will be conveyed with the aim of introducing new information that will give birth to better changes (Hana Naqiyya Nada et al, 2021; Larashati et al, 2022;Syah et al, 2021). This would be good if communication is a process where someone transfers stimuli which are usually symbols of words to change other people's behavior for the better, in this case is related to waste management in the school community.…”
Section: Introductionmentioning
confidence: 99%
“…This causes the next generation to have good attitudes and knowledge towards herpetofauna. A teacher is obliged to educate students to be knowledgeable and sensitive to the environment, thereby making them have a better attitude towards natural resources (Larashati et al, 2022).…”
Section: Knowledge Of Herpetofaunamentioning
confidence: 99%